2020
DOI: 10.3390/w12030793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photooxidation on Nanofiltration Membrane Fouling During Wastewater Treatment from the Confectionery Industry

Abstract: The research in this article aimed to present the possibilities of wastewater treatment coming from the confectionery plant in the nanofiltration (NF) process and the use of photooxidation to mitigate membrane fouling. The process was carried out initially in a dead-end flow system, where the most favorable membrane was selected. Next, the purification efficiency and blocking intensity of this membrane in the system were compared with cross flow. The next research involved the use of a photolytic oxidation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…These membranes also presented regions with different colors on their surfaces ( Figure S3, Supplementary Data ) and significant changes in FTIR spectra after exposure to UV radiation ( Figure 4 I and Figure 5 G, respectively). The FTIR spectra for these two polyamide membranes show that DK and BW are much more similar to each other than with NYLON, with the difference that BW is a polyamide thin film composite (TFC) and DK is a skin layer polyamide, coated with a hydrophilic neutral layer rich in –OH groups, with peaks between 3000 and 2700 cm −1 [ 45 , 46 , 47 ]. The commercial polyamide TFC and skin layer membranes are typically composed of three layers: a supported web of polyester, a polysulfone porous mid-layer, and a full aromatic polyamide cover layer [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…These membranes also presented regions with different colors on their surfaces ( Figure S3, Supplementary Data ) and significant changes in FTIR spectra after exposure to UV radiation ( Figure 4 I and Figure 5 G, respectively). The FTIR spectra for these two polyamide membranes show that DK and BW are much more similar to each other than with NYLON, with the difference that BW is a polyamide thin film composite (TFC) and DK is a skin layer polyamide, coated with a hydrophilic neutral layer rich in –OH groups, with peaks between 3000 and 2700 cm −1 [ 45 , 46 , 47 ]. The commercial polyamide TFC and skin layer membranes are typically composed of three layers: a supported web of polyester, a polysulfone porous mid-layer, and a full aromatic polyamide cover layer [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Membrane surface properties affected the membrane fouling mechanism and treatments were required to minimise the interactions between membrane surface and feed components [ 43 ]. For example, the effect of photooxidation treatment on nanofiltration membranes was investigated and it was concluded that it decreased the fouling phenomenon [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for other fouling studies, the one carried out by Marszałek et al [47] is based on the treatment of a nanofiltration membrane exposed to photooxidation in order to achieve a reduction in fouling. The fouling factor values for reversible and irreversible aging are approximately 0.…”
Section: Fouling Study and Membrane Deteriorationmentioning
confidence: 99%